E-097 Use of the Catalyst 5 Distal Access Catheter for Treatment of Intracranial Aneurysms: The First North American Experience. (29th July 2016) - Colby, G; Lin, L; Xu, R; Bender, M; Jiang, B; Lubelski, D; Coon, A
Abstract : Introduction: Distal intracranial support systems provide a safe and stable foundation during endovascular approaches to intracranial aneurysms. Increased catheter support allows for precise manipulation of microcatheters/devices, critical when dealing with distal targets, larger device-delivery systems, and increased vessel tortuosity. The Navien and Neuron catheters were developed to meet this demand. Here, we report the first published experience using the AXS Catalyst 5 catheter (Stryker), the newest next-generation distal access catheter. Methods: A single-center aneurysm database was reviewed to identify patients who underwent endovascular embolization with the Catalyst 5 (Figure 1 ). Patient demographics, equipment utilized, cervical ICA tortuosity, intraprocedural catheter positions, and periprocedural complications were documented. Results: 32 patients underwent 36 embolizations of 40 aneurysms (Table 1 ). The average age was 57.9 ± 13.7. 5 (13.9%) were male. 38 (95%) aneurysms were located anteriorly. 36 (90%) were small aneurysms, 1 (2.5%) was a large aneurysm, and 3 (7.5%) were giant, with an average size of 6.9 mm. 32 patients received a total of 40 pipeline embolization devices (Table 2), 2 received the WEB embolization device, and 3 patients received coils. The Catalyst was used with the Marksman microcatheter in 3 (8.3%) cases, and the VIA microcatheter in 34 (94.4%) cases. The Catalyst was successfully advanced in all cases (Figure 2), with the distal tip located in the petrous ICA 1 (2.7%), proximal cavernous 6 (16.7), distal cavernous/clinoidal 24 (66.7%), ophthalmic 1 (2.7%), communicating 1 (2.7), distal ACA 1 (2.7%), and distal vertebral artery 2 (5.4%). No patients experienced iatrogenic vessel dissection or other complications related to the catheter. Conclusions: The Catalyst 5 is an adept distal access catheter for cerebral aneurysm embolization with facile utility in the deployment of PEDs, WEB devices, as well as traditional aneurysm coiling. This catheter has outstanding trackability and stability during device deployment, and is a useful option to have when achieving distal access and support in an atraumatic fashion in the treatment of intracranial aneurysms. Disclosures: G. Colby: None. L. Lin: None. R. Xu: None. M. Bender: None. B. Jiang: None. D. Lubelski: None. A. Coon: None.